The effect of jet-lag on serum concentrations of thyroid stimulating hormone and prolactin : a case report - Gungoren, Merve Sibel (Array, 2020)
Introduction: This case report is about the importance of sleeping status for analysis of thyroid hormone stimulating hormone (TSH) and prolactin (PRL) which arose from discordant results of a patient who was referred for serum TSH and PRL testing within 12-hour period after an intercontinental flight. Case description: An adult male patient was admitted to our laboratory for serum TSH and PRL tests and came back questioning the accuracy of his previous results. Further investigations: A new analysis with a new sample was offered. His new results were not consistent with his previous results. What happened: It was revealed that the night before the first sampling, he travelled back to Turkey from The United States of America and came to testing within 12 hours after the arrival. Discussion: Sleeping status is one of the factors that can affect laboratory results. Intercontinental flights causing jet-lag can alter the secretions of TSH and PRL which are predominantly modulated by thyrotropin-releasing hormone (TRH). Main lesson: Travel history and sleeping status are important factors to be evaluated prior sampling for hormone analysis. Patients must be informed about the importance of sampling timing.